THE DEVELOPMENT MODEL OF JUNIOR HIGH SCHOOL TEACHER PERFORMANCE BASED ON THE ACEH QANUN OF EDUCATION ORGANIZATION - Aswad, Musriadi; Jalaluddin, Jalaluddin; Hambali, Hambali; Nasrun, Nasrun; Ansary, Khairil (Jurnal Visipena, 2024)
This study identifies the factors underlying the development of junior high school teacher performance in Banda Aceh, focusing on the efforts of the city government in developing teacher performance. The methods used are case studies and phenomenology, with primary data collection through interviews, observations, and questionnaires, as well as secondary data from literature reviews. Before the development program, only 60% of teachers had a bachelor's degree in education, but after two years of professional initiatives, this figure increased to 85%. Classroom observations showed a 30% increase in student engagement, and 75% of teachers felt more confident after attending subject training. The survey showed a 40% increase in the use of innovative post-training teaching methods, as well as a 20% increase in student test scores in schools implementing the program. These findings underscore the importance of strategic policies, in accordance with Qanun Aceh No. 9 of 2015, to ensure continuous improvement in the quality of education.